Yabuu Eeruwok dan Abelom Eeruwok: Aktualisasi Nilai-Nilai Kearifan Lokal Suku Lani dalam Proses Pelayanan Publik di Kabupaten Puncak Jaya - Tumiran Tumiran; Akbar Silo; Yosephina Ohoiwutun; Vince Tebay; Pawennari Hijjang; Mardi Adi Armin (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
The research aims to describe the actualization of Lani Tribe’s local wisdom in the context of governmental public services in Puncak Jaya Regency, Central Papua Province. This research uses a qualitative descriptive approach to explain in depth the local wisdom of Lani tribe, its relevance to the principles of public service and its actualization in public service practice in Puncak Jaya Regency. Data were obtained from in-depth interviews and literature review. The result of research shows that Lani tribe has local wisdom known as yabuu eeruwok and abelom eeruwok. Both forms of local wisdom have universal values so that they are relevant and can mutually strengthen the principles of modern public services, such as the New Public Service. This research also shows that the values of yabuu eeruwok and abelom eeruwok have become the motto and slogan of government administration in Puncak Jaya Regency. This indicates that these two values have been actualized in public service practices in Puncak Jaya Regency.